Margaret Chase Smith Library 2015 Student Essay Contest: In the Heart of Immigration Debate—Mercy is Sorely Missed - Tyutyunnyk, Diana (Maine Policy Review, 2016)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. In this issue, we feature the three prize-winning essays as the Margaret Chase Smith Essay. The 2015 essay prompt asked students to weigh in with their opinions about what current U.S. immigration policy should be in light of the historical backdrop of alternating cycles of welcome and wariness toward foreigners. First place prize winner Diana Tyutyunnyk brings in her personal experiences as an immigrant from the Ukraine, raising the important question of mercy as America deals with the sometimes-divisive issues around immigration.